Designing a Payroll System Database for Staff of the Informatics Engineering Department of Universitas Muhammadiyah Yogyakarta - Rizky Putri, Nisrina Akbar; Riyadi, Slamet; Kurnianti, Aprilia (Emerging Information Science and Technology, 2020)
The development of a staff payroll system aims to create a system that can help an administrator recapitulate attendance and payroll data of Informatics Engineering (IE) Department staff quickly and accurately. Such a development requires a database. The database design is divided into four stages: requirement collection and analysis, conceptual database design, logical database design, and physical database design. Design testing was performed on the database by testing the access policies, anomaly check, and view check. The results reveal that the proposed system worked well did not encounter anomalies.